An electrochemical sensor for detecting marbofloxacin and a preparation method and application thereof

CN122983154APending Publication Date: 2026-10-27WUHAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610886891.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]到目前为止,传统的检测马波沙星的方法,如高效液相色谱法(HPLC)和液相色谱-质谱法(LC-MS/MS),虽然准确,但由于其复杂性、高成本和对专业设备和训练有素的人员的要求而受到阻碍

Benefits of technology

[0016]本发明的有益效果为:本发明提供的电化学传感器,其中,多壁碳纳米管和FDM-150金属有机框架构成有机金属骨架的整体均匀修饰在玻碳电极表面,铂纳米粒子均匀负载在复合材料表面。在FDM-150和多壁碳纳米管中间形成高效的电子运输通道,多壁碳纳米管具有优异的电子传导性,能够增强电子转移效率,增加导电率。利用FDM-150对小分子的高效富集能力和π-π堆积作用,可以大量吸附游离的马波沙星。铂纳米粒子具有高度的电催化活性,能够选择性催化马波沙星的电化学氧化反应,显著降低反应过电位,增强与马波沙星的分子亲和力,提高马波沙星的氧化峰电流响应。三组分的协同作用实现了吸附富集、导电增强和催化放大的完美统一,可以起到协同催化作用,提高马波沙星的检测能力,实现了对马波沙星的高灵敏度、低检测限的电化学检测。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122983154A_ABST
    Figure CN122983154A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an electrochemical sensor for detecting marbofloxacin and application of the electrochemical sensor. The electrochemical sensor comprises a multi-walled carbon nanotube and FDM-150 metal organic framework, and the multi-walled carbon nanotube and the FDM-150 metal organic framework are uniformly modified on a surface of a glassy carbon electrode to form an organic metal framework. An electron transport channel is formed in the FDM-150. The multi-walled carbon nanotube has excellent electron conductivity, can enhance electron transfer efficiency and increase conductivity. The FDM-150 has high efficient enrichment capacity for small molecules and a pi-pi stacking effect, can adsorb a large amount of free marbofloxacin, and platinum nanoparticles can be selectively catalyzed to enhance molecular affinity with marbofloxacin and improve detection capacity of marbofloxacin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of detection technology, and in particular to an electrochemical sensor for detecting marbofloxacin, its preparation method, and its application. Background Technology

[0002] Marbofloxacin is a synthetic third-generation fluoroquinolone antibiotic widely used in veterinary clinics due to its broad-spectrum antibacterial activity, good tissue penetration, and relatively low side effects. It is primarily used to treat respiratory, digestive, and urinary tract infections in animals such as pigs, cattle, dogs, and cats. However, the overuse or improper use of antibiotics has led to marbofloxacin residues in animal-derived foods (such as milk and muscle tissue). Marbofloxacin contains a piperazine ring side chain, exhibiting high lipid solubility and bioavailability. Among its various metabolites, parent marbofloxacin is particularly important due to its high toxicity and widespread presence in veterinary drug residues. Marbofloxacin is considered one of the most hazardous veterinary drug residues due to its strong redox activity; acute exposure can lead to severe hepatotoxicity and nephrotoxicity. The widespread presence of marbofloxacin in freshwater systems poses a significant threat to the environment and public health. Marbofloxacin has a strong tendency to bioaccumulate in aquatic organisms, and its toxicity increases with the food chain, ultimately affecting wildlife, livestock, and humans. Acute exposure to marbofloxacin can cause severe liver and kidney toxicity, while low-level chronic exposure may induce allergic reactions, nephrotoxicity, and joint damage. More seriously, it may lead to the development of drug-resistant strains, posing a potential threat to human public health. Furthermore, marbofloxacin can manifest as symptoms ranging from headache and abdominal pain to serious consequences such as liver failure. To address these risks, regulatory agencies in various countries have established stringent maximum residue limits (MRLs). The urgent need for effective monitoring and detection technologies underscores the need to develop new and more sensitive marbofloxacin detection sensors.

[0003] Traditional methods for detecting marbofloxacin, such as high-performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS / MS), while accurate, are hampered by their complexity, high cost, and requirements for specialized equipment and trained personnel. These factors limit their use in field settings, particularly during food safety emergencies or in remote areas with limited laboratory facilities. Given the increasing frequency of veterinary drug residue incidents and the associated health risks, there is an urgent need for innovative detection methods that are not only sensitive and specific but also rapid, cost-effective, and user-friendly. Such methods would enable real-time monitoring of environmental and food safety, allowing for timely intervention and mitigation of toxin exposure. Differential pulse voltammetry (DPV) has attracted particular interest as an improved signal sensing method in electrochemical biosensors due to its advantages of high sensitivity, low background noise, and rapid response. DPV detection reveals a significant increase in peak current due to the specific adsorption of the analyte onto the surface of the modified layer.

[0004] Therefore, establishing a highly sensitive and accurate electrochemical detection method for mabofloxacin is of great significance for the development of rapid detection products in the future. Summary of the Invention

[0005] The main objective of this invention is to propose an electrochemical sensor for detecting marbofloxacin, its preparation method, and its application, aiming to provide an electrochemical sensor with good stability, high sensitivity, and a wide linear range.

[0006] To achieve the above objectives, this invention proposes a method for preparing PtNPs / FDM-150 / MWCNTs nanocomposite materials, comprising the following steps: S1. Preparation of FDM-150 / MWCNTs composite material: Multi-walled carbon nanotubes were ultrasonically dissolved and dispersed to form a uniform suspension. Ammonia solution, gallium nitrate, catechol and hexahydroxytriphenylene were dissolved in the suspension in sequence, and then a hydrothermal reaction was carried out. After the reaction was completed, the reaction product was centrifuged, washed and dried in sequence to obtain FDM-150 / MWCNTs composite material. S2, Platinum nanoparticle loading: The FDM-150 / MWCNTs composite material obtained in step S1 was dispersed in deionized water, and chloroplatinic acid solution was added to allow for full reaction. After the reaction was completed, sodium borohydride solution was added dropwise to the reaction solution to continue the reaction and obtain the reaction product. The reaction product was centrifuged, washed and dried in sequence to obtain the PtNPs / FDM-150 / MWCNTs nanocomposite material.

[0007] Further, in step S1, the mass ratio of multi-walled carbon nanotubes: ammonia solution: gallium nitrate: catechol: hexahydroxytriphenylene = 10: 200: 51: 110: 65.

[0008] The PtNPs / FDM-150 / MWCNTs nanocomposite material obtained by the above preparation method.

[0009] Application of PtNPs / FDM-150 / MWCNTs nanocomposite material as a modifying layer in the preparation of an electrochemical sensor for detecting marbofloxacin.

[0010] A method for preparing an electrochemical sensor for measuring marbofloxacin includes the following steps: After ultrasonically dissolving the PtNPs / FDM-150 / MWCNTs nanocomposite material obtained by the above preparation method, a perfluorosulfonic acid-based polymer was added, dispersed evenly, and then drop-coated onto the surface of the electrode material. After natural drying, an electrochemical sensor was obtained.

[0011] Furthermore, based on mass, the ratio of PtNPs / FDM-150 / MWCNTs nanocomposite material to perfluorosulfonic acid-based polymer is 1:1; the amount used for drop coating is 2~20uL.

[0012] Furthermore, the electrode material is a glassy carbon electrode.

[0013] Furthermore, the electrode material needs to undergo pretreatment operations such as grinding, multiple rinsing and drying before use.

[0014] The electrochemical sensor prepared by the above method.

[0015] The above-mentioned electrochemical sensor is used to detect the concentration of marbofloxacin.

[0016] The beneficial effects of this invention are as follows: The electrochemical sensor provided by this invention comprises a metal-organic framework consisting of multi-walled carbon nanotubes and an FDM-150 metal-organic framework uniformly modified on the surface of a glassy carbon electrode, with platinum nanoparticles uniformly loaded on the surface of the composite material. A highly efficient electron transport channel is formed between the FDM-150 and the multi-walled carbon nanotubes. The multi-walled carbon nanotubes possess excellent electronic conductivity, enhancing electron transfer efficiency and increasing conductivity. Utilizing the highly efficient enrichment capacity of FDM-150 for small molecules and its π-π stacking effect, a large amount of free marbofloxacin can be adsorbed. The platinum nanoparticles exhibit high electrocatalytic activity, selectively catalyzing the electrochemical oxidation reaction of marbofloxacin, significantly reducing the reaction overpotential, enhancing the molecular affinity for marbofloxacin, and improving the oxidation peak current response of marbofloxacin. The synergistic effect of the three components achieves a perfect unity of adsorption enrichment, enhanced conductivity, and catalytic amplification, resulting in a synergistic catalytic effect that improves the detection capability of marbofloxacin, achieving high-sensitivity, low-detection-limit electrochemical detection of marbofloxacin. Attached Figure Description

[0017] Figure 1 The flowchart below shows the process of preparing the electrochemical sensor according to the present invention. Figure 2 This is a scanning electron microscope image of the modification layer material in the electrochemical sensor provided in Embodiment 1 of the present invention; Figure 3 These are X-ray diffraction comparison images of the three materials used in this invention; Figure 4 This is a comparison of the Fourier transform infrared spectra of the three materials of this invention; Figure 5 Linear relationship graph of different concentrations of mabofloxacin obtained using the electrochemical sensor in Example 2 of this invention; Figure 6 This is a standard curve of the relationship between mabofloxacin concentration and current value obtained using the electrochemical sensor in Example 2 of this invention; Figure 7 A scanning electron microscope image of FDM-150 in the electrochemical sensor provided in Example 1 of this invention; Figure 8 Differential pulse voltammetry detection of mabofloxacin using electrochemical sensors with different modified layers. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0019] Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or a solution that simultaneously satisfies A and B. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.

[0020] Figure 1 The diagram illustrates the fabrication and application pathway of the electrochemical sensor of this invention.

[0021] The first aspect of this invention is to protect a method for preparing a PtNPs / FDM-150 / MWCNTs nanocomposite material, comprising the following steps: S1. Preparation of FDM-150 / MWCNTs composite material: Multi-walled carbon nanotubes were dispersed in deionized water and ultrasonically treated to form a uniform suspension. Ammonia solution, gallium nitrate and catechol were added to the suspension in sequence and stirred to form a clear mixed solution. Then, hexahydroxytriphenylene was added and ultrasonically treated. The mixture was transferred to a capped glass vial and reacted in an 80°C constant temperature oven for 24 h. After the reaction was completed, the black solid product was collected by centrifugation and solvent exchanged three times with deionized water. After vacuum drying, a black powdery FDM-150 / MWCNTs composite material was obtained.

[0022] In this step, the mass ratio of multi-walled carbon nanotubes: ammonia solution: gallium nitrate: catechol: hexahydroxytriphenylene = 10 : 200 : 51 : 110 : 65.

[0023] The conditions for ultrasonic treatment of multi-walled carbon nanotubes are: ultrasonic dispersion in deionized water for 10 min to form a uniform suspension, with an ultrasonic power of 180~200W. The conditions for ultrasonic treatment of hexahydroxytriphenylene were: ultrasonic treatment for 10 min after adding the reaction mixture, with an ultrasonic power of 180~200W. The vacuum drying conditions were as follows: drying in a vacuum drying oven at 60°C for 12 hours.

[0024] In this invention, multi-walled carbon nanotubes (MWCNTs) are one-dimensional carbon nanomaterials. MWCNTs treated with ultrasound exhibit excellent electrical conductivity, a large effective surface area, and good mechanical stability. During hydrothermal synthesis, gallium nitrate, catechol, and hexahydroxytriphenylene react to obtain FDM-150 nanoparticles. Simultaneously, the MWCNTs serve as a conductive network and structural support, providing a uniformly dispersed matrix for the FDM-150 nanoparticles. This leads to the formation of a highly ordered three-dimensional interconnected network structure—the FDM-150 metal-organic framework—on the surface of the MWCNTs. The FDM-150 metal-organic framework possesses the unique structural characteristics of a combination of metal-organic frameworks (MOFs) and hydrogen-bonded organic frameworks (HOFs), along with an ultra-high specific surface area and tunable pore size structure. It exhibits the ability to efficiently enrich small molecules, adsorbing large quantities of free marbofloxacin molecules from solution through physical adsorption and π-π stacking interactions, thereby enriching marbofloxacin and promoting subsequent electrochemical detection reactions.

[0025] In this invention, the composite of multi-walled carbon nanotubes and FDM-150 material not only makes up for the poor conductivity of FDM-150 material and establishes an efficient electron migration pathway, but also enhances the adsorption capacity for aromatic organic molecules such as marbofloxacin through π-π conjugation.

[0026] S2. Loading Platinum Nanoparticles: The FDM-150 / MWCNTs composite material obtained in step S1 was dispersed in deionized water, and chloroplatinic acid solution was added. The mixture was stirred continuously at room temperature for 2 h to allow the platinum precursor to be fully adsorbed. Subsequently, sodium borohydride solution was slowly added dropwise under ice-water bath conditions. The reaction was stirred for 4 h to ensure complete reduction of platinum ions. The reaction product was collected by centrifugation, washed multiple times with deionized water and ethanol, and finally dried in a vacuum drying oven at 60℃ for 12 h to obtain a black powdery PtNPs / FDM-150 / MWCNTs nanocomposite material.

[0027] In this invention, the ratio of FDM-150 / MWCNTs composite material, chloroplatinic acid solution, and sodium borohydride solution by mass is 1:10:100. The concentration of the chloroplatinic acid solution is 1 wt%.

[0028] In this invention, platinum nanoparticles (PtNPs) are a typical noble metal catalyst with excellent biocompatibility and superior catalytic efficiency. PtNPs are uniformly loaded onto the surface of an FDM-150 / MWCNTs composite material via an in-situ reduction method. PtNPs possess a unique localized surface plasmon resonance effect and high electrocatalytic activity, significantly reducing the overpotential of the electrochemical oxidation reaction of marbofloxacin, promoting electron transfer, effectively enhancing the electrochemical signal response to marbofloxacin, and achieving selective catalytic oxidation of the target molecule.

[0029] The second thing this invention aims to protect is the PtNPs / FDM-150 / MWCNTs nanocomposite material obtained by the above preparation method.

[0030] The third aspect of this invention is to protect the application of PtNPs / FDM-150 / MWCNTs nanocomposite material as an electrochemical sensor for the detection of marbofloxacin.

[0031] The modification layer material of the present invention has the following synergistic mechanism: (1) The physical interaction between the mabofloxacin molecule and the FDM-150 metal-organic framework enables efficient adsorption and enrichment; (2) The excellent conductivity of multi-walled carbon nanotubes provides a fast electron transfer channel; (3) The electrocatalytic activity of platinum nanoparticles enhances the catalytic reaction and the intensity of the electrochemical signal, thereby achieving high sensitivity, wide linear range and low detection limit of the electrochemical detection of mabofloxacin.

[0032] The fourth aspect of this invention is a method for preparing an electrochemical sensor for detecting marbofloxacin, comprising the following steps: After ultrasonically dissolving the PtNPs / FDM-150 / MWCNTs nanocomposite material prepared above, a perfluorosulfonic acid polymer (Nafion) was added and dispersed evenly. The mixture was then drop-coated onto the surface of the electrode material and naturally dried at 25°C to obtain the electrochemical sensor (PtNPs / FDM-150 / MWCNTs / GCE).

[0033] In this invention, the ratio of PtNPs / FDM-150 / MWCNTs nanocomposite material to Nafion is 1:1 by mass. The concentration of the perfluorosulfonic acid polymer is 10 wt%. The amount used for drop coating is 2~20 μL, preferably 5.0 μL.

[0034] Preferably, the electrode material is a glassy carbon electrode, and the electrode material needs to undergo pretreatment operations such as polishing, multiple rinsing and drying before use. Specifically, the glassy carbon electrode is polished sequentially with 0.3 μm and 0.05 μm alumina Al2O3 polishing powder respectively. After polishing, the glassy carbon electrode is rinsed with ultrapure water and anhydrous ethanol, and cyclic voltammetry is performed in 0.5 M sulfuric acid solution until the signal is stable. After drying, it is ready for use. This polishing and cleaning treatment makes the prepared electrochemical sensor more sensitive and the adhesion of the material drop-on on the surface to the electrode stronger.

[0035] The fifth thing this invention aims to protect is the electrochemical sensor obtained by the above preparation method.

[0036] The electrochemical sensor provided by this invention comprises a nanocomposite material consisting of multi-walled carbon nanotubes, an FDM-150 metal-organic framework, and platinum nanoparticles, uniformly modified on the surface of a glassy carbon electrode. This forms a highly efficient electron transport channel between the multi-walled carbon nanotubes and the FDM-150. The multi-walled carbon nanotubes possess excellent electronic conductivity, enhancing electron transfer efficiency and increasing conductivity. Utilizing the highly efficient enrichment capacity of FDM-150 for small molecules and its π-π stacking effect, a large amount of free marbofloxacin can be adsorbed. The platinum nanoparticles exhibit significant electrocatalytic activity, significantly reducing the overpotential of the marbofloxacin oxidation reaction, promoting electron transfer, and thus enhancing catalytic amplification, thereby improving the detection capability and sensitivity of marbofloxacin.

[0037] The sixth aspect of this invention is the method for detecting marbofloxacin using the aforementioned electrochemical sensor, comprising the following steps: S1. Dilute the marbofloxacin standard with phosphate buffer to obtain multiple standard solutions of different concentrations, enrich them on the modified layer of the electrochemical sensor, and perform differential pulse voltammetry to obtain differential pulse voltammetry curves. S2. Construct a standard curve of mabofloxacin concentration-current with the concentration of mabofloxacin as the x-axis and the current value in the differential pulse voltammetry graph as the y-axis. S3. After the sample to be tested is adsorbed through the modified layer, multiple current values ​​are obtained by electrochemical detection. The current values ​​are selected, and the concentration of marbofloxacin in the sample to be tested is calculated based on the marbofloxacin concentration-current value standard curve.

[0038] The above method is an electrochemical analysis method that utilizes changes in potential and current pulses to measure the peak current and reactant concentration of an electrochemical reaction. The principle of differential pulse voltammetry is to use three electrodes—a working electrode, a reference electrode, and a counter electrode—to measure changes in potential and current, primarily for measuring minute currents. It can be used to detect the concentration of small molecules, such as marbofloxacin. The method for detecting marbofloxacin described in this invention, combined with a modified layer material to establish a rapid detection method, has the advantages of simple operation, simple electrode modification, high sensitivity, and no need for complex sample pretreatment. It also offers advantages such as low detection cost, rapid detection, and low requirements for detection instruments.

[0039] It should be noted that as the concentration of marbofloxacin increases, the peak current increases significantly, thus the corresponding concentration of marbofloxacin in the test solution can be obtained by comparing with the standard curve.

[0040] <Example 1> A method for preparing an electrochemical sensor for detecting marbofloxacin includes the following steps: S1. Preparation of FDM-150 / MWCNTs composite material: 10.0 mg of multi-walled carbon nanotube suspension was added to 50 mL of ultrapure water, and then 51.0 mg of gallium nitrate, 110 mg of catechol and 65.0 mg of hexahydroxytriphenylene were added to obtain a mixture. The mixture was stirred and then added to a reaction vessel containing polytetrafluoroethylene. The mixture was heated in an oven at 80°C for 24 h, cooled to room temperature, and the precipitate was obtained by centrifugation. The precipitate was subjected to solvent exchange three times with deionized water and then dried in a vacuum drying oven at 60°C for 12 hours to obtain black powdered FDM-150 / MWCNTs composite material. S2. Platinum-loaded nanoparticles: 20.0 mg of the synthesized FDM-150 / MWCNTs composite material was dispersed in 10.0 mL of deionized water, and 0.2 mL of chloroplatinic acid solution (1 wt%) was added. The mixture was stirred continuously at room temperature for 2 h to allow the platinum precursor to be fully adsorbed. Subsequently, 2.0 mL of freshly prepared sodium borohydride solution (40 mmol / L) was slowly added dropwise under ice-water bath conditions, and the reaction was stirred for 4 h. The reaction product was collected by centrifugation, washed multiple times with deionized water and ethanol, and finally dried in a vacuum drying oven at 60 °C for 12 h to obtain a black powder, namely the PtNPs / FDM-150 / MWCNTs nanocomposite material. S3. Take 1 mg of the above PtNPs / FDM-150 / MWCNTs nanocomposite material and add it to deionized water. Sonicate for 1 min, then add 10 μL of 10 wt% Nafion solution and disperse evenly. Drop 5.0 μL onto the surface of the glassy carbon electrode and let it dry naturally at 25℃ to obtain the electrochemical sensor PtNPs / FDM-150 / MWCNTs / GCE.

[0041] The scanning electron microscope (SEM) image of the PtNPs / FDM-150 / MWCNTs nanocomposite material prepared in this embodiment is attached. Figure 2 As shown. By Figure 2 The results indicate that the combined PtNPs / FDM-150 / MWCNTs nanocomposite possesses a polyhedral structure and a tubular structure of one-dimensional carbon nanotubes. MWCNTs are uniformly wound on the surface and within the crystal gaps of FDM-150, with a neat surface and nanoparticles tightly stacked together to form a three-dimensional interconnected network structure, resulting in a high specific surface area and excellent electrical conductivity. This demonstrates that the addition of multi-walled carbon nanotubes did not disrupt the structure of FDM-150. The polyhedral morphology of FDM-150 remains intact, with fine particles distributed on the crystal surface and carbon nanotube walls, corresponding to the successfully loaded platinum nanoparticles. This confirms the successful preparation of the PtNPs / FDM-150 / MWCNTs nanocomposite.

[0042] X-ray diffraction comparison images of FDM-150 metal-organic framework and PtNPs / FDM-150 / MWCNTs nanocomposite materials are shown below. Figure 3 As shown.

[0043] Pure FDM-150 exhibits a broad diffraction envelope centered at 2θ = 6.94°, 12.5°, and 15.76°, attributed to its amorphous to semi-crystalline organic framework with (110), (100), and (310) crystal planes. A distinct (200) strong diffraction peak appears at 11.22° in FDM-150, confirming the formation of a crystal framework with long-range molecular order, consistent with previous reports. Hybridization with MWCNTs introduces a sharp peak at 2θ = 26.2°, corresponding to the (002) graphite plane of the MWCNTs. A weak, broad peak (39.7°) corresponding to Pt (111) is observed in the ternary composite, consistent with the smallly dispersed PtNPs (JCPDS No. 04-0802). No significant loss of FDM-150 characteristics indicates that the crystal framework is largely preserved.

[0044] The Fourier transform infrared (FTIR) spectra of the three materials—FDM-150 metal-organic framework, multi-walled carbon nanotubes, and platinum nanoparticles—in the PtNPs / FDM-150 / MWCNTs nanocomposite material are compared as follows: Figure 4 As shown.

[0045] Depend on Figure 4 It can be seen that pure FDM-150 is at approximately 3150 cm. –1 (N–H stretching vibration of the amine group), 1610 cm –1 (C=C aromatic vibration), 1450 cm –1 (C–N bending vibration) and 1230 cm –1 Characteristic peaks were observed at the C–O stretching vibration of the phenolic group. These characteristics remained unchanged in the spectra of FDM-150 / MWCNTs and PtNPs / FDM-150 / MWCNTs, confirming that the core coordination bonds in FDM-150 remained intact during MWCNT entanglement and Pt loading. No new peaks (e.g., around 550 cm⁻¹) were observed. –1 The Pt–O peak shift or position shift indicates the presence of non-covalent interactions. This observation confirms that the core molecular structure and functional groups of the FDM-150 framework were preserved during composite material preparation and PtNP loading.

[0046] <Example 2> A method for detecting marbofloxacin using the above-mentioned electrochemical sensor includes the following steps: S1. Dilute marbofloxacin with phosphate buffer to prepare standard solutions of different concentrations (0.01~500 μM). S2. The electrochemical sensor prepared in Example 1 above was placed in standard solutions of marbofloxacin at different concentrations and mixed for adsorption at room temperature for 5 min, so that marbofloxacin was adsorbed on the electrochemical sensor. Then it was placed in an electrochemical detection cell and detected by differential pulse voltammetry to determine the electrochemical response curves at different marbofloxacin concentrations. S3. Using the peak current of marbofloxacin as the direct response signal, within the detection concentration range, the magnitude of the peak current and the concentration of marbofloxacin have a logarithmic linear relationship, thus constructing a standard curve for the marbofloxacin electrochemical sensor.

[0047] As attached Figure 5-6 As shown, the linear detection range of marbofloxacin concentration is 0.01–500 μM, exhibiting advantages such as simple electrode modification and high sensitivity, with a detection limit of 0.0023 μM for marbofloxacin. With increasing marbofloxacin concentration in the standard solution, marbofloxacin more readily binds to the PtNPs / FDM-150 / MWCNTs nanocomposite material and is adsorbed onto the electrode surface. The piperazine ring side chain in the marbofloxacin molecule undergoes an electrochemical oxidation reaction on the electrode surface, leading to a change in the electron transfer efficiency in the PtNPs / FDM-150 / MWCNTs structure, allowing electrons to reach the electrode surface more freely, ultimately resulting in an increase in peak current. Therefore, the concentration of marbofloxacin can be indirectly detected through changes in electrochemical signal.

[0048] Data shows that the mabofloxacin electrochemical sensor provided by this invention can successfully detect low concentrations of mabofloxacin, and has a wide linear range and a low detection limit.

[0049] <Example 3> The detection of marbofloxacin in bullfrog and crucian carp samples includes the following steps: Marbofloxacin standards were added to crucian carp and bullfrog muscle samples at concentrations of 1.0 μM, 5.0 μM, and 10.0 μM, respectively. The samples were then filtered using a 0.22 μm filter membrane. Differential pulse voltammetry was performed using the electrochemical sensor prepared in Example 1 under the same conditions as in Example 2. Note: All measurements were performed at room temperature (25 ± 2°C), and each concentration was measured in triplicate (n = 3 times).

[0050] The standard curve based on the results of Example 2 I p = 6.7591 × lg C + 9.5204 ( R 2= 0.9912), and the measured values ​​for the three concentration levels were (1.0 ± 0.03) μM, (5.0 ± 0.11) μM and (10.0 ± 0.15) μM, respectively, with an average recovery rate of 97.0% - 101.7%.

[0051] The results showed that the peak current was well correlated with the concentration of marbofloxacin within the linear range of 0.01–500 μM; the recovery rate of marbofloxacin in complex matrices (aquatic product muscle tissue) met the detection requirements.

[0052] The purpose of this embodiment is to verify that the PtNPs / FDM-150 / MWCNTs / GCE prepared in Example 1 has high sensitivity for differential pulse voltammetric detection of marbofloxacin.

[0053] <Comparative Example 1> This comparative example only uses glassy carbon electrodes to prepare an electrochemical sensor, specifically: An electrochemical sensor (BareGCE) was prepared by drop-coating 10 μL of a 10 wt% Nafion solution onto the surface of a glassy carbon electrode.

[0054] <Comparative Example 2> This comparative example only uses FDM-150 metal-organic framework to modify a glassy carbon electrode to prepare an electrochemical sensor, specifically: S1. Weigh 51.0 mg gallium nitrate (approximately 0.20 mmol) and 110 mg catechol (1.0 mmol) and dissolve them in a mixed solution of 20 mL ultrapure water and 0.20 mL ammonia solution (25 wt% NH3) to obtain solution A. Dissolve 65.0 mg hexahydroxytriphenylene (0.20 mmol) in a solvent, namely ultrapure water, to obtain solution B. Mix solutions A and B and stir, then add them to a reactor lined with polytetrafluoroethylene and heat in an oven at 80 °C for 24 h to obtain FDM-150 metal-organic framework. S2. Take 1 mg of the above FDM-150 metal-organic framework and add it to deionized water. Sonicate for 1 min, then add 10 μL of 10 wt% Nafion solution and disperse evenly. Drop 5.0 μL onto the surface of the glassy carbon electrode and let it dry naturally at 25 °C to obtain the electrochemical sensor (FDM-15 / GCE).

[0055] The scanning electron microscope image of the FDM-150 metal-organic framework prepared in this comparative example is shown below. Figure 7 As shown, this indicates that the crystal size of pure FDM-150 is approximately 1 μm, the nanomaterial has a regular polyhedral structure, the crystal surface is smooth and the edges are clear, exhibiting good crystallinity.

[0056] <Comparative Example 3> In this comparative example, only the glassy carbon electrode was modified with FDM-150 / MWCNTs composite material to prepare an electrochemical sensor. Platinum nanoparticles were not loaded. The rest of the operation was the same as in Example 1 to prepare the electrochemical sensor (FDM-150 / MWCNTs / GCE).

[0057] The electrochemical sensors prepared in Example 1 and Comparative Examples 1-3 were used to measure 200 μM mabofloxacin. The peak current of the electrochemical sensors was tested, and the blank phosphate buffer solution (PtNPs / FDM-150 / MWCNTs / GCE(blank)) measured in Example 1 was used as a control group. The test results are attached. Figure 8 As shown, Comparative Example 1, using a bare glassy carbon electrode (GCE), exhibited a very weak peak current in its electrochemical response to marbofloxacin (MAR). Compared to Comparative Example 1, Comparative Example 3, with its electrode modified with FDM-150 and multi-walled carbon nanotubes, showed a significantly higher peak current for MAR. In Comparative Example 3, the peak current at a MAR concentration of 200 μM was significantly higher than that of Comparative Examples 1 and 4. In Example 1, the PtNPs / FDM-150 / MWCNTs / GCE with added platinum nanoparticles showed the strongest peak current response to marbofloxacin, exhibiting the highest sensitivity. This is because the combination of high-concentration MAR with PtNPs / FDM-150 / MWCNTs fully utilized the synergistic effect of the three components, significantly enhancing electron transfer efficiency and catalytic activity.

[0058] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.

Claims

1. A method for preparing a PtNPs / FDM-150 / MWCNTs nanocomposite material, characterized in that, Includes the following steps: S1. Preparation of FDM-150 / MWCNTs composite material: Multi-walled carbon nanotubes were ultrasonically dissolved and dispersed to form a uniform suspension. Ammonia solution, gallium nitrate, catechol and hexahydroxytriphenylene were dissolved in the suspension in sequence, and then a hydrothermal reaction was carried out. After the reaction was completed, the reaction product was centrifuged, washed and dried in sequence to obtain FDM-150 / MWCNTs composite material. S2, Platinum nanoparticle loading: The FDM-150 / MWCNTs composite material obtained in step S1 was dispersed in deionized water, and chloroplatinic acid solution was added to allow for full reaction. After the reaction was completed, sodium borohydride solution was added dropwise to the reaction solution to continue the reaction and obtain the reaction product. The reaction product was centrifuged, washed and dried in sequence to obtain the PtNPs / FDM-150 / MWCNTs nanocomposite material.

2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of multi-walled carbon nanotubes: ammonia solution: gallium nitrate: catechol: hexahydroxytriphenylene = 10: 200: 51: 110:

65.

3. The preparation method according to claim 1, characterized in that, In step S2, the ratio of FDM-150 / MWCNTs composite material: chloroplatinic acid solution: sodium borohydride solution is 1:10:100 by mass.

4. The PtNPs / FDM-150 / MWCNTs nanocomposite material obtained by the preparation method described in claim 1 or 2.

5. The application of the PtNPs / FDM-150 / MWCNTs nanocomposite material as described in claim 4 as a modifying layer in the preparation of an electrochemical sensor for detecting marbofloxacin.

6. A method for preparing an electrochemical sensor for measuring marbofloxacin, characterized in that, Includes the following steps: After ultrasonically dissolving the PtNPs / FDM-150 / MWCNTs nanocomposite material obtained by the preparation method described in claim 1 or 2, a perfluorosulfonic acid-based polymer is added, dispersed evenly, and then drop-coated onto the surface of the electrode material. After natural drying, an electrochemical sensor is obtained.

7. The preparation method according to claim 6, characterized in that, Based on mass, the ratio of PtNPs / FDM-150 / MWCNTs nanocomposite material to perfluorosulfonic acid-based polymer is 1:1; the amount used for drop coating is 2~20uL.

8. The preparation method according to claim 6, characterized in that, The electrode material is a glassy carbon electrode, which needs to undergo pretreatment operations such as grinding, multiple rinsing and drying before use.

9. An electrochemical sensor obtained by the preparation method according to any one of claims 5-8.

10. The application of the electrochemical sensor as described in claim 9 in detecting the concentration of marbofloxacin.